Preparation method of phase change microcapsule with photothermal conversion function
By introducing graphene oxide cladding into phase change microcapsules, the problems of single energy source and low energy storage efficiency of traditional phase change microcapsules are solved, photothermal conversion and efficient heat storage and release are achieved, and the application of phase change microcapsules materials is expanded.
Patent Information
- Application Number
- CN202510157831.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-01
AI Technical Summary
Traditional phase-change microcapsules have a single energy source, and their energy storage efficiency is extremely low in low temperature environments. They can only passively store and release heat, lacking the photothermal conversion function.
Paraffin-based phase-change microcapsules coated with silica encapsulation are modified by silane coupling agent and grafted with graphene oxide to achieve photothermal conversion and efficient heat storage and release.
The photothermal conversion from solar energy to thermal energy is realized, and the thermal energy utilization efficiency is improved through high thermal conductivity graphene oxide, broadening the energy source and application of phase-change microcapsule materials.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of microcapsule preparation, and in particular to a method for preparing phase-change microcapsules with light-heat conversion function. Background Art
[0002] In the late 19th century, industrial production development entered a period of rapid growth, and many industrialization and modernization goals were achieved. However, with the rapid development of industrialization and urbanization, energy demand continues to increase. But fossil fuels are limited and non-renewable, and human society is facing a major and threatening energy crisis. At the same time, the extensive use of traditional fossil fuels will lead to a sudden increase in greenhouse gases such as carbon dioxide in the atmosphere, causing global climate change, energy shortages, and hindering the development of a sustainable society. Among the many technologies, developing new clean energy and improving energy efficiency are two main ways. Among them, improving energy efficiency as a way to achieve lower technical difficulty and better thermal management has received widespread attention from researchers.
[0003] Phase change materials can store and release energy by changing their phases. In most cases, the phase change process of phase change materials is reversible. During the phase change process, phase change materials will store and release energy. Energy can be provided to the low-energy phase of the material, which will undergo a phase change under the action of external conditions, thereby transforming into a high-energy phase. And by transforming the low-energy phase to the high-energy phase, energy storage and release are achieved. The transformation from the low-energy phase to the high-energy phase can achieve energy storage. Conversely, energy can also be released by the transformation from the high-energy phase to the low-energy phase. Different phase change materials have different phase changes, such as solid-liquid, solid-gas, and solid-solid phase change processes. In addition, the transition between different phases is accompanied by changes in physical and chemical properties. The solid-liquid phase change process will cause volume changes, and the liquid has fluidity, which will impose certain restrictions on the application of phase change materials. Therefore, the phase change material is encapsulated in a dense shell material through microencapsulation technology to form a core-shell structure, and a phase change microcapsule material is prepared to overcome this limitation. Microencapsulation technology perfectly solves the leakage problem and volume change defect of solid-liquid phase change materials, and expands the application scope of phase change materials.
[0004] In recent years, inorganic shell materials including silicon dioxide, calcium carbonate, titanium dioxide, etc. have been successfully used in the encapsulation process of phase change microcapsules. The dense inorganic encapsulation shell formed provides a good encapsulation effect for the phase change material, ensuring the shape stability and long-term durability of the phase change material. However, traditional phase change microcapsule materials can only passively store and release heat, and the energy storage efficiency is extremely low in an environment where the temperature is low and the phase change temperature is not reached. Therefore, in order to further expand the energy source of traditional phase change microcapsule materials and improve their energy conversion efficiency, it is necessary to develop a phase change microcapsule with photothermal conversion function to provide a new method for achieving photothermal conversion and efficient energy utilization. Summary of the invention
[0005] In view of the deficiency of the existing phase change microcapsules in that the energy source is single, the present invention provides a method for preparing paraffin-based phase change microcapsules encapsulated with graphene oxide coated with silica and having a photothermal conversion function. The present invention prepares phase change microcapsules with photothermal and anti-leakage capabilities through coating technology, with paraffin as the core material and silica as the inner shell material, and the silica outer shell is modified with a silane coupling agent and then graphene oxide is grafted on the silica layer. The introduction of graphene oxide enables the synthesized microcapsules to have good photothermal capacity and heat storage and release capacity, and can realize the photothermal conversion of solar energy into thermal energy and perform efficient heat storage and release.
[0006] The present invention is achieved through the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing phase change microcapsules using silicon dioxide as an encapsulation shell material, comprising the following steps:
[0008] (1) Construction of a non-aqueous dispersion type "oil-in-water" emulsion system: paraffin wax and a silica precursor are mixed, heated and continuously stirred to form a uniform and stable oil phase solution, and an organic solvent and a first surfactant are mixed at the same temperature. After the first surfactant is completely dissolved, the oil phase solution is added and continuously stirred to complete the construction of a non-aqueous dispersion type "oil-in-water" emulsion system;
[0009] (2) The silica precursor undergoes an interfacial polycondensation reaction in the paraffin micelles: a certain amount of deionized water is mixed with a concentrated hydrochloric acid solution to obtain a hydrochloric acid solution of a specific concentration, and a certain amount of the obtained hydrochloric acid solution of the specific concentration is added at a certain dropwise acceleration to the non-aqueous dispersed "water-in-oil" emulsion system obtained in step (1), and the reaction temperature and stirring speed are kept unchanged to carry out the reaction. After a period of reaction, the reaction is completed, filtered, washed, and dried in an oven at 40°C until the solvent is completely evaporated to obtain silica phase change microcapsules with a "core-shell" structure.
[0010] Preferably, in step (1), the paraffin wax is a mixture of hydrocarbons having a carbon number of about 30 to 32 (for example, n-triacontane, n-triacontane, n-dotriacontane or a mixture of the three substances); the organic solvent is formamide; the first surfactant is hexadecyl ammonium bromide; and the silicon dioxide precursor is tetraethyl silicate.
[0011] Preferably, in step (1), the ratio of the added amounts of the paraffin wax, the silica precursor, the organic solvent and the first surfactant is 1-2.5 g: 2-5 mL: 30-60 mL: 0.30-0.50 g.
[0012] Preferably, in step (1), the heating temperature is 60° C.; the stirring speed is 400 rpm; and the continuous stirring time is 7 h.
[0013] Preferably, in step (2), the added volume ratio of the deionized water, concentrated hydrochloric acid solution, specific hydrochloric acid solution and non-aqueous dispersible "oil-in-water" emulsion is 40-60 mL: 3-8 mL: 20-40 mL: 50-100 mL; the concentration of the concentrated hydrochloric acid is 12 M / L; the concentration of the specific concentration hydrochloric acid solution is 1 M / L; the dripping speed is 500 μL / min; and the reaction time is 4 hours.
[0014] A second aspect of the present invention provides a method for preparing graphene oxide-coated microcapsules, comprising the following steps:
[0015] (1) Amination modification of phase change microcapsules: The obtained silica-encapsulated phase change microcapsules, a second surfactant, an organic solvent and deionized water are mixed, and stirred for a period of time at a certain temperature to obtain a microcapsule turbid liquid. After the modification reaction is completed, the liquid is filtered, washed and dried to obtain the aminated silica-encapsulated phase change microcapsules;
[0016] (2) Graphene oxide coated with aminated modified phase change microcapsules: graphene oxide and ethanol solution are mixed by ultrasound for a period of time; at the same time, the aminated modified phase change microcapsules prepared in step (1) are added to the ethanol solution, and magnetic stirring is performed at room temperature. The graphene oxide solution is added to the microcapsule ethanol solution and magnetic stirring is performed for a period of time, and then filtered, washed, and dried to prepare phase change microcapsules with photothermal conversion function;
[0017] Preferably, the ratio of the added amounts of the phase change microcapsules, the second surfactant, the organic solvent and the deionized water in step (1) is: 0.5-1.0 g: 300-600 µL: 40-80 mL: 10-30 mL; the second surfactant is the silane coupling agent KH-550; the organic solvent is N,N-dimethylformamide; the reaction temperature is 30°C; the magnetic stirring time is 1 h; and the stirring speed is 220-300 rpm.
[0018] Preferably, the ratio of the added amounts of graphene oxide, amino-modified phase change microcapsules and ethanol solution in step (2) is: 20-30 mg: 0.14-0.40 g: 100-120 mL; the concentration of the ethanol solution is 75 wt %; the ultrasonic time is 5-10 min; the magnetic stirring time is 1 h; and the magnetic stirring speed is 100-200 rpm.
[0019] The beneficial effects of this invention are:
[0020] 1. The phase-change microcapsules encapsulated with silicon dioxide and graphene oxide with light-to-heat conversion function prepared by the present invention do not leak during the melting and crystallization process due to the presence of the shell layer, while still maintaining a thermal conductivity of more than 101 J·g -1 This is attributed to the complete core-shell microstructure of the phase change microcapsule, which provides sufficient internal space for the long-chain molecular movement of alkanes and provides good protection for the migration and leakage of molecules, allowing paraffin to achieve phase transition to store and release energy without leakage. In addition, the dense inorganic shell structure can delay the loss of phase change materials and enhance the thermal stability and thermal conductivity of the microcapsule.
[0021] 2. The phase-change microcapsules encapsulated with graphene oxide coated with silica and having a photothermal conversion function prepared by the present invention introduce graphene oxide as a component of the shell modification material. Graphene oxide absorbs and converts solar energy, and the sensible heat generated can quickly increase the temperature of the inorganic silica shell layer, thereby causing the core material paraffin to undergo a phase transition to achieve energy storage and release. In addition, the high thermal conductivity of graphene oxide can greatly improve the thermal conduction of the microcapsules, which is beneficial to the rapid thermal conversion of the phase-change microcapsules and improves the thermal energy utilization efficiency of the phase-change microcapsules.
[0022] 3. The present invention uses solar energy as a source of thermal energy and innovatively designs a phase-change microcapsule material that simultaneously has both photothermal conversion and thermal energy storage and release, providing a new idea for the efficient conversion and storage of solar thermal energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : Scanning electron microscope image of the phase change microcapsule with light-to-heat conversion function of the present invention;
[0024] Figure 2 : DSC graph of the phase-change microcapsule with light-to-heat conversion function of the present invention;
[0025] Figure 3 : Photothermal curve diagram of the phase change microcapsule with photothermal conversion function of the present invention. DETAILED DESCRIPTION
[0026] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0027] As described in the background technology, in recent years, inorganic materials such as silicon dioxide, calcium carbonate, titanium dioxide, etc. have been successfully applied as coating shell materials for phase change materials, and have the ability to be further modified. Traditional phase change microcapsule materials only have the function of storing and releasing external heat, and the energy source is relatively limited. In a certain high and low temperature conversion environment, it can fully store and release external heat. However, in an environment where the external temperature is lower than the phase change temperature, it will stagnate the storage and release of external heat. Based on this situation, traditional phase change microcapsule materials have certain limitations in application.
[0028] Based on this, the present invention provides a method for preparing paraffin-based phase-change microcapsules encapsulated by graphene oxide-coated silica. The paraffin-based phase-change microcapsules encapsulated by graphene oxide-coated silica with photothermal performance are of a "core-multi-layer shell" structure: paraffin is used as the core and dense silica is used as the inner shell to form a silica phase-change microcapsule with a "core-shell" structure. At the same time, graphene oxide is coated on the outside of the silica phase-change microcapsules to obtain microcapsules with a spherical "core-multi-layer shell" structure. When preparing the outer shell, tetraethyl silicate and paraffin are first mixed and stirred to form an oil phase, and then formamide and hexadecyl ammonium bromide are added for emulsification. Sol-gelation of tetraethyl silicate is initiated by dripping hydrochloric acid, and a dense shell is formed on the surface of the micelle. Subsequently, the outer silica shell layer is aminated by a silane coupling agent, and the phase-change microcapsules are coated by the amino-grafted graphene oxide on the outside, and then a graphene oxide coating layer is formed.
[0029] This structure has a good encapsulation effect on the paraffin of the phase change material, and provides good protection against the molecular migration and leakage of the paraffin when absorbing heat, so that the phase change microcapsule material can continuously and stably store and release heat, and maintain good shape stability. The paraffin-based phase change microcapsules encapsulated by graphene oxide coated with silica, and the introduction of graphene oxide as a modified material component on the silica shell layer, can absorb solar energy and quickly convert heat to achieve the photothermal conversion function through graphene oxide, broadening the energy source and application of phase change microcapsule materials.
[0030] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific examples. If the specific experimental conditions are not specified in the examples, they are usually in accordance with conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, unless otherwise specified, can be obtained through commercial channels.
[0031] Example
[0032] (1) Construction of non-aqueous dispersion type "oil-in-water" emulsion system
[0033] Add 2 g paraffin and 2.5 mL tetraethyl silicate into a 250 mL round-bottom flask, adjust the temperature to 60°C, and continue stirring at 400 rpm for 30 min to obtain a stable and uniform oil phase solution; in another 100 mL beaker, dissolve 0.45 g hexadecyl ammonium bromide in 30 mL formamide, stir at the same 60°C until the hexadecyl ammonium bromide is completely dissolved, then pour it into the 250 mL round-bottom flask, and continue stirring for 7 h to complete the construction of the non-aqueous dispersion type "water-in-oil" emulsion system.
[0034] (2) Interfacial polycondensation of silica precursor on the surface of paraffin micelles
[0035] In a beaker, 55 mL of deionized water and 5 mL of concentrated hydrochloric acid were mixed to obtain a 1 M hydrochloric acid solution. The reaction temperature in step (1) was kept constant at 60°C, and then 30 mL of the 1 M hydrochloric acid solution was slowly dripped into the three-necked reaction bottle through a microfluidic pump syringe, and the dripping speed was adjusted to 500 μL / min. Under continuous stirring, tetraethyl silicate was induced to sol-gel on the surface of paraffin micelles. After the reaction was completed, the obtained mixture was filtered, washed with deionized water, and the product was dried until the solvent was completely evaporated to obtain silica phase change microcapsules.
[0036] (3) Amination modification of phase change microcapsules
[0037] 0.6 g of the silica-encapsulated phase-change microcapsules obtained in step (2), 600 μL of silane coupling agent KH-550, 40 mL of N,N-dimethylacetamide and 20 mL of deionized water were added into a 100 mL beaker, and the mixture was stirred at 260 rpm at 30 °C for 6 h to obtain a microcapsule turbid solution. After the modification reaction was completed, the mixture was filtered, washed and dried to obtain amino-modified silica-encapsulated phase-change microcapsules.
[0038] (4) Graphene oxide-coated aminated phase change microcapsules
[0039] 20 mg of graphene oxide was mixed with 20 mL of ethanol solution and then ultrasonicated for 5 min. Meanwhile, 0.3 g of amino-modified phase change microcapsules prepared in step (3) were added into 100 mL of ethanol solution and magnetically stirred at room temperature. The ultrasonically treated graphene oxide solution was added into the microcapsule ethanol solution and magnetically stirred at 150 rpm for 1 h. The mixture was then filtered, washed and dried to obtain phase change microcapsules with photothermal conversion function (named S3).
[0040] Comparative Example 1
[0041] The difference from step (1) in the embodiment is that the silicon dioxide precursor tetraethyl silicate is not added, and the pure paraffin microspheres after emulsification are obtained, which are named S0.
[0042] Comparative Example 2
[0043] The difference from step (1) in the embodiment is that the phase change core material paraffin in the silica phase change microcapsule is not added, and the silica microspheres are prepared by sol-gel, which is named S1.
[0044] Comparative Example 3
[0045] The difference from step (4) in the embodiment is that no graphene oxide is added, and silica-encapsulated paraffin phase change microcapsules not coated with graphene oxide are obtained, which are named S2.
[0046] Test example
[0047] 1. Phase change enthalpy test of microcapsules
[0048] The phase change enthalpy of S0, S1, S2 and the phase change microcapsules with photothermal conversion function was obtained by differential scanning calorimetry (DSC) test. The temperature was raised from 0°C to 100°C at a rate of 10°C per minute and then lowered to 0°C at the same rate. The area was obtained by integration as the corresponding enthalpy value. Figure 2 From the phase change enthalpy data, it can be seen that paraffin microspheres (S0) have a phase change enthalpy of 152.3 J·g -1 The phase change enthalpy value of silica microspheres (S1) as non-phase change materials does not have phase change heat storage capacity and does not show endothermic peaks and exothermic peaks. The phase change microcapsules (S2) encapsulated by silica shells still have a phase change enthalpy of 127 J·g -1 The phase change enthalpy value of the phase change microcapsules (S3) coated with graphene oxide still maintains 101 J·g -1 The phase change enthalpy value proves that the prepared photothermal conversion microcapsules can exhibit good thermal energy storage capacity in the photothermal process.
[0049] 2. Xenon lamp simulated sunlight photothermal conversion test of microcapsules
[0050] A xenon lamp solar simulator was used to evaluate the photothermal conversion capability and photothermal storage performance of the microcapsule samples. The phase change microcapsule samples of S0 and S3 were placed in a culture dish, and then the dish was exposed to an irradiation intensity of 300 mW / cm 2 After a period of irradiation, the beaker was removed from the solar simulator and then cooled naturally to room temperature. The temperature change of the microcapsule sample was monitored by a thermometer during the whole process.
[0051] Figure 3The graph shows the temperature of the test sample changing with the illumination and cooling time. The phase change microcapsules (S3) and paraffin microspheres (S0) with photothermal conversion function are used as control samples. Under the irradiation of simulated sunlight, the temperature rise rate of the phase change microcapsules with photothermal conversion function is significantly faster than that of the paraffin microspheres. The temperature platform of the melting phase transition appears at about 55.3 °C. After the melting process is completed, the temperature continues to rise and finally reaches 76.3 °C. During natural cooling, the temperature drop is slowed down and a temperature platform appears at about 54.6 °C due to the exothermic effect of the phase change core material paraffin inside the prepared photothermal phase change microcapsule from the molten state to the solidified state. After the crystallization process is completed, the temperature continues to drop to room temperature. In addition, it can be seen that the paraffin microspheres as the control sample cannot reach their phase change temperature under the condition of xenon lamp as the cold light source, so no phase change platform appears during the cooling process, and its temperature continues to drop to room temperature in a short time. The photothermal test results also prove that the prepared phase-change microcapsules with photothermal conversion function have good photothermal conversion and phase change storage and release thermal energy capabilities, and have good application prospects in photothermal and phase change thermal energy storage.
[0052] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing phase-change microcapsules with photothermal conversion function, characterized in that: The following steps are involved: (1) Construction of a non-aqueous dispersion type "oil-in-water" emulsion system: paraffin wax and a silica precursor are mixed, heated to a certain temperature and continuously stirred until a uniform and stable oil phase solution is obtained; at the same temperature, an organic solvent and a first surfactant are stirred and mixed; after the first surfactant is completely dissolved, it is added to the oil phase solution for mixing and stirring to form a non-aqueous dispersion type "oil-in-water" emulsion system; the paraffin wax is a hydrocarbon mixture having a carbon number of about 30 to 32 (for example, n-triacontane, n-triacontane, n-dotriacontane or a mixture of the three substances); the silica precursor is tetraethyl silicate; the organic solvent is formamide; the first surfactant is hexadecyl ammonium bromide; the heating temperature is 60°C; the stirring speed is 400 rpm; the mixing and stirring time is 7 hours; (2) The silica precursor undergoes an interfacial polycondensation reaction in the paraffin micelles: deionized water and concentrated hydrochloric acid solution are stirred to obtain a hydrochloric acid solution of a certain concentration, and the hydrochloric acid solution of a certain concentration is added dropwise to the non-aqueous dispersed "water-in-oil" emulsion system obtained in step (1), and the reaction temperature and stirring speed are kept unchanged to carry out the reaction. After the reaction is completed, the silica precursor is filtered, washed, and dried in an oven at 40° C. until the solvent is completely evaporated to obtain a silica phase change microcapsule having a "core-shell" structure; the paraffin, the silica precursor, The ratio of the added amount of organic solvent and surfactant is 1-2.5g:2-5mL:30-60mL:0.30-0.50g; the added volume ratio of deionized water, concentrated hydrochloric acid and non-aqueous dispersible "water-in-oil" emulsion is 40-60mL:3-8mL:50-100mL; the concentration of the concentrated hydrochloric acid solution is 12M / L; the concentration of the certain concentration hydrochloric acid solution is 1M / L; the dripping speed is 500μL / min; the reaction time is 4h; (3) Amination modification of phase change microcapsules: the silica encapsulated phase change microcapsules obtained in step (2), the second surfactant, the organic solvent and deionized water are mixed, and stirred for a period of time at a certain temperature to obtain a microcapsule turbid liquid. After the modification reaction is completed, the liquid is filtered, washed and dried to obtain the aminated silica encapsulated phase change microcapsules; The ratio of the added amount of the phase change microcapsules, the second surfactant, the organic solvent and the deionized water is: 0.5-1.0g: 300-600μL: 40-80mL: 10-30mL; the second surfactant is silane coupling agent KH-550, and the organic solvent is N, N-dimethylformamide; the reaction temperature is 30°C, the time is 1h; the stirring speed is 220-300rpm; (4) Graphene oxide coated with aminated modified phase change microcapsules: graphene oxide and ethanol solution are mixed by ultrasound for 5 minutes; at the same time, the aminated modified phase change microcapsules prepared in step (3) are added to the ethanol solution, and magnetic stirring is performed at room temperature. The graphene oxide ethanol solution is added to the microcapsule ethanol solution and magnetic stirring is performed for 10 minutes. After that, a certain amount of the second surfactant is added and stirred for 1 hour. After that, the mixture is filtered, washed, and dried to prepare phase change microcapsules with photothermal conversion function. The added amount ratio of the graphene oxide, the aminated modified phase change microcapsules and the ethanol solution is: 20-30 mg: 0.14-0.40 g: 100-120 mL; the concentration of the ethanol solution is 75 wt%; and the magnetic stirring speed is 100-200 rpm.
2. The phase-change microcapsules with light-to-heat conversion function obtained by the preparation method of claim 1, characterized in that: The phase-change microcapsules with photothermal conversion function include silicon dioxide phase-change microcapsules and graphene oxide coated outside the silicon dioxide phase-change microcapsules. The phase-change microcapsules with photothermal conversion function are irregular spheres coated with flaky graphene oxide; the silicon dioxide phase-change microcapsules have a "core-shell" structure, with paraffin as the core and dense silicon dioxide as the shell.
Citation Information
Cited By
TiO2 / rGO heterojunction-loaded bionic sea urchin-shaped asymmetric structure composite phase change chitosan aerogel as well as preparation method and application of TiO2 / rGO heterojunction-loaded bionic sea urchin-shaped asymmetric structure composite phase change chitosan aerogel
CN121972099A
A biomimetic sea urchin-like asymmetric composite phase change chitosan aerogel supported on TiO2 / rGO heterostructure, its preparation method and application
CN121972099B
Shape-stable paraffin and silicon dioxide microcapsule phase change composite material and preparation method thereof
CN122146241A